Portrayals of Antigone in Portugal : 20th and 21st century rewritings of the Antigone myth - Morais, Carlos.; Hardwick, Lorna.; Silva, Maria de Fátima Sousa e. (Metaforms, 2017)
Portrayals of Antigone in Portugal gathers a collection of essays on the Portuguese drama rewritings of this Theban myth produced in the 20th and 21st centuries. For each of the cases analysed, the Portuguese historical, political and cultural context is described. This perspective is expanded through a dialogue with coeval European events. As concerns Portugal, this results principally in political and feminist approaches to the texts. Since the importation of the Sophoclean model is often indirect, the volume includes comparisons with intermediate sources, namely French (Cocteau, Anouilh) and Spanish (María Zambrano), which were extremely influential on the many and diversified versions written in Portugal during this period.